The Effect of Total Football Style on The Development of Tactical Performance Level In Football Primer Clubs - Essam, Athear; Nagi, Ahmed (Journal of Physical Education, 2019)
The importance of the research lies in the preparation of small sided games using total football style and its effect on skill, physical and tactical development in primer football clubs. The problem of the research lies in weak level of tactical performance thus the importance lies in developing the tactical performance of players using total football style. The research aimed at identifying the effect of small sided games using total football style on physical, skill and tactical performance level development. the researchers used the experimental method. The subjects were Baghdad club as controlling group and Al Shorta club as a controlling group 2015 – 2016. The data was collected and treated using SPSS to come up with the conclusion and recommendations.